The (New) Awakening of Soviet Jazz Culture in the 1960s - Reimann, Heli (Taylor & Francis, 2022)
Following the period of lowest political tolerance toward jazz from the late 1940s to the death of Stalin in 1953, Soviet jazz culture experienced gradual growth during Nikita Khrushchev’s Thaw. This essay argues that the jazz awakening in the 1960s was part of the shestidesyatniki (Sixtiers) movement and that legalization of jazz took place within the frameworks of Soviet leisure activities and amateur culture. In addition, the growth of Soviet jazz was influenced by American jazz diplomacy during the 1950s and 1960s, represented by Willis Conover and his Jazz Hour and the tours of the Jazz Ambassadors.
Keywords: jazz; Neuvostoliitto; musiikinhistoria